2020
DOI: 10.1098/rsos.200685
|View full text |Cite
|
Sign up to set email alerts
|

Dishonesty as a signal of trustworthiness: Honesty-Humility and trustworthy dishonesty

Abstract: Trustworthiness is a foundation of well-functioning relationships and societies, and thus often perceived as a socially normative behaviour. Correspondingly, a broad array of research found that people tend to act in a trustworthy way and signal their trustworthiness to others, and that trustworthiness is rewarded. Herein, we explore whether this motivation to behave trustworthily can have socially undesirable effects in terms of leading to dishonesty targeted at fulfilling the trustor's expectations (i.e. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 64 publications
(100 reference statements)
0
7
1
Order By: Relevance
“…Honesty–humility also uniquely predicted lying for several self-centered motivations: to avoid negative evaluation, to avoid punishment, to heighten self-presentation, to obtain a reward, and compulsive lying. Interestingly, no associations between honesty–humility and other-centered lying were identified despite previous evidence suggesting that higher honesty–humility was associated with prosocial lying to gain the trust of another person (Ścigała et al, 2020). Differences in methodologies likely explain these differences in findings.…”
Section: Resultscontrasting
confidence: 59%
See 1 more Smart Citation
“…Honesty–humility also uniquely predicted lying for several self-centered motivations: to avoid negative evaluation, to avoid punishment, to heighten self-presentation, to obtain a reward, and compulsive lying. Interestingly, no associations between honesty–humility and other-centered lying were identified despite previous evidence suggesting that higher honesty–humility was associated with prosocial lying to gain the trust of another person (Ścigała et al, 2020). Differences in methodologies likely explain these differences in findings.…”
Section: Resultscontrasting
confidence: 59%
“…Differences in methodologies likely explain these differences in findings. Ścigała et al (2020) utilized direct observation and a specific gaming scenario, whereas our study relied on self-report data of lying behavior in the past six months. Participants in our study may not have been in a situation in the recent past where lying would have helped to gain the trust of another individual.…”
Section: Resultsmentioning
confidence: 99%
“…If these ratios are unequal, individuals experience distress and are motivated to either modify their own or others' ratios, change their perceptions of the situation, or abandon the situation altogether 39,40 . In support of this theory, several studies found that people are concerned with equity and fairness, and are willing to change their present situation to restore equity [41][42][43][44] .…”
Section: Equity and Fairness Considerationsmentioning
confidence: 94%
“…Notably, previous research shows that when faced with a conflict between cooperating/benefiting others and avoiding dishonest/corrupt behaviour, people higher in Honesty-Humility tend to choose the former 39 . Furthermore-in line with the self-concept maintenance theory 17,19,40 as well as the theoretical basis of Honesty-Humility 34,38 cooperation framing should increase bribery engagement among high-Honesty-Humility individuals because it might allow them to justify bribery by drawing their attention to cooperative aspects of the bribery interaction-i.e., the aspects of the interaction that high-Honesty-Humility individuals should generally be concerned with due to their cooperative tendencies 31,32,41 .…”
Section: Introductionmentioning
confidence: 98%